ACOUSTIC METHOD OF DETERMINATION OF CONCENTRATION OF HARD ADMIXTURES - Кривенко, Галина Мирославівна; Возняк, Мирослав Петрович; Кривенко, Сергій Олександрович; Возняк, Лідія Володимирівна; Савчук, Лілія Ярославівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The presence of hard admixtures in the stream of water changes intensity of voice vibrations. A liquid which moves in a pipe creates some permanent noise background. Addition of hard admixtures results in the change of sound-level. Investigational a level of intensity of noise is depending on the spectrum of frequencies during the different concentration of hard admixtures. The analysis of research results rotined that at the permanent expense of liquid the change of acoustic description during motion of stream of slurry will enable to define a concentration in it